Hamiltonian analysis of non-relativistic non-BPS Dp-brane - J. Klusoň (Journal of High Energy Physics, 2017)
Abstract We perform Hamiltonian analysis of non-relativistic non-BPS Dp-brane. We find the constraint structure of this theory and determine corresponding equations of motion. We further discuss property of this theory at the tachyon vacuum.